2014
DOI: 10.15866/irecap.v4i4.2455
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of Raised-Cosine Wavelets for Multicarrier Systems Design

Abstract: Link to publisher's version: http: //dx.doi.org/10.15866/irecap.v4i4.2455 Citation: Anoh KOO, Mapoka TT, Abd-Alhameed RA, Ochonogor O and Jones SMR (2014) On the application of raised-cosine wavelets for multicarrier systems design. International Journal on Communications Antenna and Propagation. 4(4): 143 -150.Copyright statement: © 2014 Praise Worthy Prize S.r.l. Full-text reproduced with permission from the publisher. (IRECAP), 2014, Vol. 4, N. 4, pp. 143 -150. August 2014 ISSN 2039 -5086 On Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In [7], it was shown that wavelets have better suppressed sidelobes than conventional FFT-OFDM systems. That study did not explore other well-known wavelets, such as the orthogonal wavelets described in the literature [12], [14], [17], [20]. In the following, we demonstrate the filter response of these wavelets showing the performance of the sidelobes in Figs.…”
Section: Sidelobe Performance Of Different Mother Waveletsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7], it was shown that wavelets have better suppressed sidelobes than conventional FFT-OFDM systems. That study did not explore other well-known wavelets, such as the orthogonal wavelets described in the literature [12], [14], [17], [20]. In the following, we demonstrate the filter response of these wavelets showing the performance of the sidelobes in Figs.…”
Section: Sidelobe Performance Of Different Mother Waveletsmentioning
confidence: 99%
“…Wavelets from the orthogonal family have distortionless sidelobes [12]- [14]. We evaluate the performances of different wavelets in terms of the side-lobe performances which has the potential to influence the energy of the adjacent subbands.…”
Section: Sidelobe Performance Of Different Mother Waveletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative kernel uses the DFT tool except that there exists dilation (stretching) and translation (repositioning) of the signal coefficients. Since WT finds applications in communication systems design, WT-OFDM has been studied by different authors for wireless [13]- [16] and PLC [17], [18] systems. A major drawback in its adoption is that it is computationally inefficient and recent studies have led to different computationally efficient algorithms such as the ones reported in [9] and [19].…”
Section: A Ofdm Systems Design Using Wtmentioning
confidence: 99%